Studies of the influence of ball size and net height on table tennis trajectory distributions - Schneider, R.; Lüskow, K. F.; Kemnitz, S. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
One possible measure to increase the medial appeal of table tennis is to slow down the game by using bigger balls or higher nets. In this work, the equations of motion for table tennis balls are solved numerically on GPUs (Graphics Processing Unit) by CUDA (Compute Unified Device Architecture), which gives a very large speed-up compared to CPUs. This allows analyzing five billion different initial conditions for systematical, statistical studies of the impact of ball size and weight as well as of net height on the distribution functions of successful strokes. Hitting locations, initial spins and velocities in terms of values and directions are varied by Monte Carlo sampling and the resulting distributions of successful trajectories were analyzed. The absolute values of the translational velocities were limited to 20 to 200 km/h, the spinning velocities to 0 to 150 turns/s (topspin, sidespin and backspin were included). A ball is counted as a successful ball if it passes the net within the height limit (30 cm above the net height) and hits the other side of the table tennis table. The analysis confirms the empirical observation that the change of the ball in the year 2000 from a 38-mm to a 40-mm-ball can be compensated with other parameters such that their resulting trajectory distribution functions are nearly identical. The player`s technique compensated the larger ball size. Up to now, a further increase of the ball size is the preferred correction action to reduce the maximum velocity in table tennis rallies. A larger ball of 44 mm with small weight is one option for suppressing high velocities, coupled also to a reduction of the influence of spinning. Alternatively, an increase of the net height is possible. A small increase of the net height could be one future option, where the basic character of the game is mostly conserved, but especially the influence of the service could be reduced.